2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Occupational Safety and Health Act (OSHA) [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
The Occupational Safety and Health Act (OSHA) provides general safety standards, inspection, and posting requirements for covered employers and their workers. This is EDIS document FE408, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.